Can Collective Responsibility for Perpetrated Evil Persist over Generations? - Van Den Beld, Ton (Ethical theory and moral practice, 2002)
In the first part of the paper an argument is developed to the effect that (1) there is no moral ground for individual persons to feel responsible for or guilty about crimes of their group to which they have in no way contributed; and (2) since there is no irreducibly collective responsibility nor guilt at any time, there is no question of them persisting over time. In the second part it is argued that there is nevertheless sufficient reason for innocent individual members of a group (that persists over time) to take on responsibility and guilt for the evil other (earlier) members have committed. The reason depends on the acceptability of a particular psychological theory of personal identity.